Nuisance Ordinances and Domestic Violence - Sarah Kroeger; Giulia La Mattina (Institute of Labor Economics (IZA), 2024)
Criminal activity nuisance ordinances penalize tenants for calling emergency services in relation to certain illegal events, including domestic violence. There is a widespread concern that these policies will exert a chilling effect on the reporting of domestic violence and potentially increase the incidence and severity of domestic assaults. We exploit the sequential implementation of criminal activity nuisance ordinances by municipalities in Ohio, and estimate the direct impact of these ordinances on intimate partner homicides using a reduced form framework. We rule out an increase in intimate partner homicides following the enactment of a nuisance ordinance; in fact we estimate a negative impact. The effect is driven by a reduction in partner homicides in cities with a higher proportion of renter-occupied homes prior to the implementation of the ordinances. We do not find any evidence that the effect can be attributed to selective migration out of cities that enacted nuisance ordinances or a change in police officer reporting practices.
Keywords: J12; J18; K42; R28; 330; domestic violence; housing policy; intimate partner homicide; nuisance ordinance